2011
DOI: 10.1002/nau.21129
|View full text |Cite
|
Sign up to set email alerts
|

Bladder compliance what does it represent: Can we measure it, and is it clinically relevant?

Abstract: Methods: During a three day meeting a group of specialists discussed compliance, what it represents, how it can be measured and if it is clinically relevant.Results: Bladder compliance is the result of a mathematical calculation of volume responsible for 1 cm H2O pressure rise measured during a cystometric filling. It gives an indication on how the different mechanisms in the bladder wall react on stretching. There is a need of standardisation of measurement and suggestions for this are given in the text. Pitf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 56 publications
2
72
1
1
Order By: Relevance
“…Compliance is calculated by dividing the volume change (DV) by the change in detrusor pressure (Dp det ) (C = DV/Dp det , expressed in ml/cmH 2 O) [14]. Two standard points should be used: the start of filling and cystometric capacity or immediately before any detrusor contractions that will end the test by, for example, significant leakage [15]. The compliance was accepted as normal (detrusor pressure C20 ml/cmH 2 O) or hypocompliance (detrusor pressure \20 ml/cmH 2 O) [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance is calculated by dividing the volume change (DV) by the change in detrusor pressure (Dp det ) (C = DV/Dp det , expressed in ml/cmH 2 O) [14]. Two standard points should be used: the start of filling and cystometric capacity or immediately before any detrusor contractions that will end the test by, for example, significant leakage [15]. The compliance was accepted as normal (detrusor pressure C20 ml/cmH 2 O) or hypocompliance (detrusor pressure \20 ml/cmH 2 O) [1].…”
Section: Discussionmentioning
confidence: 99%
“…The compliance was accepted as normal (detrusor pressure C20 ml/cmH 2 O) or hypocompliance (detrusor pressure \20 ml/cmH 2 O) [1]. Detrusor overactivity, low bladder capacity, vesicoureteric reflux, high bladder weight, recent retention episodes, low bladder wall blood flow, and usage of indwelling catheters are associated with poor bladder compliance [15]. As the detrusor overactivity is more frequent in the ULSCI group, the rate of detrusor hypocompliancy was found to be higher in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the nonexistence of placebo effects in NDO studies may counteract the limited patient numbers. [13][14][15] The evaluation of the studies revealed some deficits, as clinically important parameters were either not evaluated or not reported: the impact of AM on bladder compliance, which was either not assessed or the results given were difficult to interpret due to nonuniform methodology; 42 the issue, whether AM shorten a prolonged detrusor contraction, the need for IC, exact data on the achievement of continence, for example, in-between IC, the impact of AM on UTI frequency and on QoL. This deficiency with respect to QoL may be because of the fact that many studies were conducted at a time when this issue was not yet a primary research focus.…”
Section: Discussionmentioning
confidence: 99%
“…En la cistometría se monitorizan los cambios de presión vesical durante la fase de llenado y se evalúan la sensibilidad, la capacidad, la acomodación vesical, la actividad del detrusor y la función uretral durante dicha fase. En el estudio presión-volumen se evalúan la actividad del detrusor y la función uretral durante la fase de vaciamiento (13,14). No todo paciente con LUTS requiere un estudio urodinámico completo.…”
Section: Diagnósticounclassified